2010 39th International Conference on Parallel Processing Workshops 2010
DOI: 10.1109/icppw.2010.20
|View full text |Cite
|
Sign up to set email alerts
|

FFT Algorithms Evaluation on a Homogeneous Multi-processor System-on-Chip

Abstract: This paper presents the evaluation of radix-2, radix-4 and radix-8 algorithms for N-point FFTs on a homogeneous Multi-Processor System-on-Chip, prototyped on FPGA device. The evaluation of the algorithms was done analysing profiling of the algorithms in comparison to a single processor architecture. The performance were evaluated in terms of required clock cycles, achieved speed-up and parallelization efficiency. The analysis showed for each algorithm how the parallelization efficiency grows moving from small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The system power management strategy consisted of switching off the clocks of inactive processors while data was being downloaded and switching off the clocks of idle data transfer and storage hardware while the processor was busy and without the need of continuous data supply. Besides WCDMA cell search and timing synchronisation, the study cases include FFT algorithms [20] and a generic OFDM system receiver [21] developed using plain C code and defined in a parametric way, hence adding or removing nodes from the architecture does not require re-writing the software from scratch. Moreover the study cases showed a high scalability of the algorithm mapping and a high parallelization efficiency.…”
Section: Ninesilica Architecturementioning
confidence: 99%
“…The system power management strategy consisted of switching off the clocks of inactive processors while data was being downloaded and switching off the clocks of idle data transfer and storage hardware while the processor was busy and without the need of continuous data supply. Besides WCDMA cell search and timing synchronisation, the study cases include FFT algorithms [20] and a generic OFDM system receiver [21] developed using plain C code and defined in a parametric way, hence adding or removing nodes from the architecture does not require re-writing the software from scratch. Moreover the study cases showed a high scalability of the algorithm mapping and a high parallelization efficiency.…”
Section: Ninesilica Architecturementioning
confidence: 99%
“…There are many kinds of algorithm pattern, such as Radix-2 FFT algorithm, Radix-4 FFT algorithm, Radix-8 FFT algorithm, Split-Radix FFT algorithm and so on [6] [12]. Radix-2 FFT algorithm is suitable for hardware implementation, and it is usually employed to process 2 npoint FFT operation.…”
Section: Introductionmentioning
confidence: 99%